Mainstream Complexity. Nolan’s Inception as a Case for (Amateur) Narratologists (Cinéma & Cie. Film and Media Studies Journal, 2012)
At this point in time, popular media practices (mainstream cinema, television, gaming) pro- vide surprisingly complicated multi-layered narrative structures. They urgently call for a closer analysis. The author revisits Genette’s theoretical work – in particular his reflections on metalepsis – to examine the narrative experiments now presented to viewers of main- stream cinema. What can we learn from Genette to understand these new forms of narration, their functions and the kind of experiences they create? What do they imply for our theories and theorizing on a broader level? Christopher Nolan’s Inception (2010) will be used as a case study in order to draw out some of the implications of these new developments – i.e., what Jason Mittell described as the production of films and television series for “amateur nar- ratologists.”